The Impact of Information Technology (IT) Risk Management on Strategic Agility and Organizational Performance: A Study on Small and Medium-Sized Enterprises (SMEs) in Penang, Malaysia - Sim, Poo Beng (2014)
Purpose of this research is to investigate the effect of information technology (IT) risk management in predicting organizational performance. In addition, strategic agility had been explored as a mediating factor and environmental uncertainty as a moderating factor in this research. The survey was conducted among 163 small and medium-sized enterprises (SMEs) in the State of Penang, Malaysia. In essence, this research had built a framework based on resource based view theory. The collected data was analyzed by using SPSS and SmartPLS statistical tool.